Conflict management for co‐ordination between shift teams in Shanghai subway stations. (30th November 2017) - Zhang, Xin‐an; Liu, Huihua; Shi, Yushen; Tjosvold, Dean
Abstract : Conflict among teams is inevitable in a multiteam system. Drawing on the theory of co‐operation and competition, we proposed and tested a model linking the approaches teams adopt to conflict, inter‐team co‐ordination, and multiteam system performance. Data collected from 123 operation teams in 44 subway stations in Shanghai revealed that co‐operative conflict management positively related to inter‐team co‐ordination, which in turn positively related to performance of the multiteam system. The relationship between competitive conflict management and inter‐team co‐ordination was insignificant and was moderated by co‐operative conflict management. When co‐operative conflict management was at a low level, competitive conflict management negatively related to inter‐team co‐ordination.